2021
DOI: 10.1038/s41398-021-01668-1
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral immune cell reactivity and neural response to reward in patients with depression and anhedonia

Abstract: Increased levels of peripheral cytokines have been previously associated with depression in preclinical and clinical research. Although the precise nature of peripheral immune dysfunction in depression remains unclear, evidence from animal studies points towards a dysregulated response of peripheral leukocytes as a risk factor for stress susceptibility. This study examined dynamic release of inflammatory blood factors from peripheral blood mononuclear cells (PBMC) in depressed patients and associations with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 73 publications
1
21
0
Order By: Relevance
“…Additionally, this finding fits our prior research reporting relationships between levels of various inflammatory mediators in the blood and anhedonia, as well as their associations with brain function during a reward fMRI task (6,(18)(19)(20). Complementing our works focusing on adolescence, others have shown a correlation between an LPS-induced immune cluster and anticipatory anhedonia, indexed by TEPS-A and a reward fMRI task, in adults (84). The varied cytokines contributing to different immune factors linked to anhedonia across studies is expected from the data-driven nature of factor analyses.…”
Section: New Insights Into Adrenergic-modulated Immunologic Correlate...supporting
confidence: 89%
See 3 more Smart Citations
“…Additionally, this finding fits our prior research reporting relationships between levels of various inflammatory mediators in the blood and anhedonia, as well as their associations with brain function during a reward fMRI task (6,(18)(19)(20). Complementing our works focusing on adolescence, others have shown a correlation between an LPS-induced immune cluster and anticipatory anhedonia, indexed by TEPS-A and a reward fMRI task, in adults (84). The varied cytokines contributing to different immune factors linked to anhedonia across studies is expected from the data-driven nature of factor analyses.…”
Section: New Insights Into Adrenergic-modulated Immunologic Correlate...supporting
confidence: 89%
“…While anticipatory and consummatory anhedonia quantified with clinical self-reports might share quite some variance, our study supported their divergent immunological correlates across various experimental conditions. Perhaps the distinction between anhedonia subcomponents is more apparent biologically, as suggested by works from our group and others (18,84,90).…”
Section: New Insights Into Adrenergic-modulated Immunologic Correlate...mentioning
confidence: 74%
See 2 more Smart Citations
“…Regarding the mechanisms by which inflammation affects the brain, much attention has been paid to the impact of inflammation on neurotransmitter systems and neurocircuits that regulate motivation and motor activity as well as anxiety, arousal, and alarm. Neuroimaging studies examining the impact of inflammation on neurocircuits have largely focused on subjects administered inflammatory stimuli ( Harrison et al, 2009 , 2015 , 2016 ; Eisenberger et al, 2010 ; Capuron et al, 2005 , 2012 ), but increasing data from our group and others have demonstrated that endogenous inflammation in MD (often indexed by blood concentrations of CRP) is also associated with alterations in activity of and functional connectivity (FC) within reward and motor circuits as well as circuits involving threat sensitivity that are in turn related to symptoms of anhedonia, psychomotor retardation and anxiety ( Burrows et al, 2021 ; Felger et al, 2016 ; Mehta et al, 2018 ; Rengasamy et al, 2021 ; Savitz et al, 2013 ; Yin et al, 2019 ; Costi et al, 2021 ). A wealth of evidence from clinical and laboratory animal studies supports the idea that relationships between elevated inflammatory markers and deficits in these neurocircuits are driven by the impact of circulating inflammatory cytokines and peripheral blood immune cells on the brain to reduce availability and release of monoamines, notably dopamine, and increase synaptic and extrasynaptic glutamate in the anterior cingulate cortex and basal ganglia nuclei ( Felger and Treadway, 2017 ; Felger et al, 2013a , 2013b , 2015 ; Yohn et al, 2016 ; Kitagami et al, 2003 ; Haroon et al, 2014 , 2016 , 2018b ; Walker et al, 2013 ; Dantzer and Walker, 2014 ).…”
Section: Introduction (Ahm)mentioning
confidence: 99%